Mengomunikasikan Hak Kesehatan dan Pendidikan Disabilitas: Kisah dari Penyandang Disabilitas dan Orang Tua Anak Disabilitas di Indonesia - Muhammad Novsyaroni Umar (Badan Strategi Kebijakan Hukum, 2025)
Indonesians with disabilities experience socio-cultural problems that result in disparities in disability rights fulfilment, particularly in accessing equal education and healthcare. In response to such problems, disability activism has been undertaken, and nowadays is increasingly mediated by social media, specifically Instagram. This study intends to shine a light on individual and parental perspectives in communicating disability rights, drawing on the co-cultural communication theory, which classifies people with disabilities as a non-dominant group in society. Diverse disability stakeholders including people with disabilities and parents of children with disabilities participated in focus group discussions and semi-structured formal and informal interviews. Using digital autoethnographic methods, qualitative content analysis was also employed to examine their Instagram content on disability topics. This study focuses on how participants raise awareness of disability inclusion and communicate disability rights within the domain of education and healthcare. This study also emphasizes the efficacy of Instagram in mediating disability rights activism in Indonesia and its impact on the participants and their disability communities. The results show that while the assertive accommodation and non-assertive assimilation strategies are applicable in offline and online settings, the non-assertive accommodation strategy is particularly prevalent in enhancing digital disability representation. These collective actions contribute to advancing the fulfilment of those rights.